Celebrating Robin Watkins' Third Birthday at Home - Watkins, Howard::::::::: (1985)
Front: Devon Bleile-Kratzer, Annie Bleile-Kratzer, Robin Watkins; Back: Adam Watkins and Seth Tilley all in family room